Transformasi Kebijakan Moneter Islam dalam Menghadapi Tantangan Keuangan Global dan Digitalisasi Ekonomi Nasional Syariah Modern - Putri Fania Ardianti; Allya Zahra Putri Nasution; Muhammad Arfan Harahap (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This research aims to analyze the transformation of Islamic monetary policy in responding to global financial challenges and the acceleration of digitalization within the modern national sharia economy. Changes in the global economic landscape, instability in the international financial system, and rapid technological advancement require adaptive and sustainable Islamic monetary policy innovations. This study employs a qualitative approach using a literature review of scientific journals, regulations, and official reports from national and international Islamic financial institutions. The findings indicate that Islamic monetary policy in Indonesia has undergone significant transformation through the strengthening of sharia-based monetary instruments, optimization of the role of Islamic banking, and the integration of digital technology into the Islamic financial system. The digitalization of the sharia economy plays a crucial role in improving the efficiency of monetary policy transmission, enhancing financial inclusion, and maintaining national financial system stability. Nevertheless, several challenges remain, including regulatory harmonization, digital infrastructure readiness, and public literacy in Islamic finance. This research concludes that the transformation of Islamic monetary policy based on sharia principles and digital innovation is a strategic approach to safeguarding economic stability, enhancing competitiveness, and supporting inclusive and sustainable national economic growth.